Penerapan Strategi Time-Based Competition pada Perusahaan Manufaktur - Myrna Nurahma (Universitas Islam Indonesia, 2004)
Time is the secret weapon of business. Advantages in response time provide leverage for all the other competitive differences that make up a company’s overall competitive advantage. The new generation of competitors is obtaining remarkable results by focusing its organizations on flexibility and responsiveness. Time-based competition is a competitive strategy that seeks to compress the time required to propose, develop, produce, market and deliver the products to the customers. Several tools can be used in applying this strategy in manufacture industry, such as, Total Quality Management, Quality Function Deployment, Work Team Empowerment, Taguchi Methods, and Just-in TimeKeywords: Time-based Competition, Total Quality Management, Quality Function Deployment, Work Team Empowerment, Taguchi Methods, Just-in Time.